Pengaruh Gratis Ongkos Kirim Cash on Delivery dan Customer Review terhadap Keputusan Pembelian di E-Commerce Shopee - M Akmal Ramadhani; Khalil Nawawi; Tika Kartika (STIKes Ibnu Sina Ajibarang, 2025)
The rapid development of technology has led to increased use of the internet. Nowadays, almost the entire population of Indonesia uses the internet for online shopping. Through e-commerce, consumers can order products. This research was conducted to test the effect of Free Shipping, cash on delivery and customer reviews on e-commerce Shoppe purchase decisions on Uika Bogor Islamic Economics Students. This study uses quantitative research methods. The population in this study is a student of Islamic Economics UIKA Bogor with a sample of 105 people. Data collection techniques through observation, interviews and questionnaires, data analysis techniques used are multiple linear regression analysis. This study uses the SPSS 26.0 program. The results of hypothesis testing obtained Value t count Free Shipping (2.167) > t table (1.983), t count cash on delivery (2.871) > t table (1.983) and t count customer review (2.787) > t table (1.983) with significant level < 0.05. Thus H_1, H_2 and H_3 are accepted. Simultaneous testing results (test F), obtained the value of F count (16.918) > F table (2.69) with a significant level of 0.000 < 0.05. The results of this study can be concluded that free shipping, cash on delivery and customer reviews affect the decision to purchase online at e-commerce Shopee Islamic Economics Students UIKA Bogor.